Pengembangan Sumber dan Evaluasi Pembelajaran Sekolah Dasar Menggunakan Moodle Berbasis Virtual Machine - Soelistijanto, Bambang; Hernawan, Agung; Hadhiatma, Agung (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Information technology-based learning has become a significant method to enhance the quality of education. Information technology allows students to learn without being limited by time and space. Students can also study and practice independently according to their capacity and needs. E-learning is a learning methodology that requires information technology. One of the information technologies that has been used for learning is Moodle. Moodle is a learning management system